The Views of University Supervisors and School Advisors on Pre-service Science Teachers’ Ability to Construct Scientific Explanations of a Rajabhat University in the Northeastern Group - Auansrimuang, Wichuta; Pruekpramool, Chaninan (Rajapark Journal, 2023)
This research aimed to study the views of university supervisors and school advisors on pre-service science teachers' ability to construct scientific explanations at a Rajabhat University in the Northeastern Group. This research employed a qualitative research methodology using interpretative phenomenology based on Heidegger. The key informants were 8 university supervisors and school advisors with 7-9 years of experience in teaching science and supervising pre-service science teachers using purposive selection. The data were collected through in-depth interviews using a semi-structured interview protocol. The data were analyzed based on Leonard's process. The credibility of the data was verified using the triangulation method. The findings revealed the views of university supervisors and school advisors based on their experiences that pre-service science teachers could construct scientific explanations composed of three components, which were claim, evidence, and reasoning, in the form of short sentences that were not completely connected. The pre-service science teachers could identify the correct claim according to the scientific concepts if it is the concept that they are learning or have recently learned. They obtained evidence from the inquiry process through experiments and searching for information related to the claim, but it was insufficient, resulting in incomplete reasoning. Inquiry-based learning, hands-on activities, practicing to present the experimental results, and summarizing the scientific concept more often could help to promote pre-service science teachers' ability to construct scientific explanations.